Experimental and Numerical Study of Slug-Flow Velocity Inside Microchannels Through In Situ Optical Monitoring - Samuele Moscato; Emanuela Cutuli; Massimo Camarda; Maide Bucolo (Micromachines)
Miniaturization and reliable, real-time, non-invasive monitoring are essential for investigating microfluidic processes in Lab-on-a-Chip (LoC) systems. Progress in this field is driven by three complementary approaches: analytical modeling, computational fluid dynamics (CFD) simulations, and experimental validation techniques. In this study, we present an on-chip experimental method for estimating the slug-flow velocity in microchannels through in situ optical monitoring. Slug flow involving two immiscible fluids was investigated under both liquid–liquid and gas–liquid conditions via an extensive experimental campaign. The measured velocities were used to determine the slug length and key dimensionless parameters, including the Reynolds number and Capillary number. A comparison with analytical models and CFD simulations revealed significant discrepancies, particularly in gas–liquid flows. These differences are mainly attributed to factors such as gas compressibility, pressure fluctuations, the presence of a liquid film, and leakage flows, all of which substantially affect flow dynamics. Notably, the percentage error in liquid–liquid flows was lower than that in gas–liquid flows, largely due to the incompressibility assumption inherent in the model. The high-frequency monitoring capability of the proposed method enables in situ mapping of evolving multiphase structures, offering valuable insights into slug-flow dynamics and transient phenomena that are often difficult to capture using conventional measurement techniques.